PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, KOMPETENSI, DAN MOTIVASI INTRINSIK TERHADAP KINERJA PEGAWAI (Studi Kasus: Direktorat Jenderal Administrasi Hukum Umum Kementerian Hukum Dan Ham Ri) - Nurliza, N; D.R. Manurung, Antonius (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to examine and analyze the effect of information technology utilizationon the employee performance ,the effect of competency on the employee performance, the effect of intrinsic motivation on the performance of employees, and the effect of information technology utilization,competency, and intrinsic motivation simultaneously to the performance of employees at the Directorate General of Legal Administration. This reserch used survey methodwhile collected samplesof 221 questionnaires. The data analysis used model test using LISREL application.The results showed that the variables information technology utilization, competency and intrinsic motivation partially positive and significant impact on performance of employees. The result of study indicate that the information technology utilization has positive effect onthe employee performance, the competency has positive effect on the employee performance, the intrinsic motivation has positive effect on the employee performance. While simultaneously, all three endogenous variables (free) the information technology utilization, competency and intrinsic motivation and significant positive effect on theemployee performance at Directorate General of Legal Administration